A Case Study on The Quantitative Determination of Fluoride in Drinking Water using The Colorimetric Method with UV-Vis Spectrophotometry - Nisa', Salma Alifatun; Salfiah, Salma; Arianty, Alya Dwi; Hidayah, Fitria Fatichatul (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, Indonesia, 2025)
Drinking water is something that is consumed by the general public every day. One of the contents contained in drinking water is fluoride which can have a negative impact on humans if the level exceeds 1 mg/L. The objective of this study is twofold: firstly, to identify and calculate the concentration of fluoride in bottled drinking water samples, and secondly, to determine the suitability of consuming the samples. An analysis of fluoride levels was conducted on five drinking water samples. This analysis was performed using a UV-Vis spectrophotometer at a wavelength of 570 nm. The reagent used was sodium 1-parasulfophenylazo 20-1,8-dihydroxy-3-6-naphthalene (SPADNS). The test is based on the reaction of fluoride and zirconium, which results in the absorption of colour by the former and the formation of a colourless complex anion by the latter. The observation is made indirectly by observing the reduction of the absorption of the SPADNS-zirconyl acid reagent complex, rather than the absorption of the reagent to which fluoride ions have been added. The measurement results indicate that the five samples exhibit fluoride levels below 1 mg/L, with a range of 0.054 - 0.560 mg/L. In accordance with the standards outlined in SNI 3553:2015 concerning Mineral Water, the analysed drinking water samples are deemed to be in compliance with stipulated parameters. This is due to the fact that the concentration of total dissolved solids in the water samples does not exceed 1.0 milligrams per litre (mg/L).